Establishing the environmental and economic benefits of applying advanced thermal hydrolysis to existing anaerobic digesters in the Western Cape, South Africa - Potts, Wesley (Department of Civil Engineering, 2022)
The treatment of sewage by wastewater treatment works (WWTW) generates a solids byproduct stream requiring treatment and disposal. The waste sludges generated are rich in essential nutrients and energy, and present an opportunity to turn a waste stream into a resource. Retrofitting a thermal hydrolysis process (THP) to existing anaerobic digestion (AD) sludge treatment has proven itself globally as a reliable means of increasing treatment capacity and creating a final product that is non-hazardous. This allows for more sustainable sludge disposal options. However, THP has not yet been proven in a South African context. This research carried out a comparative desktop case study of the existing AD facility at the Cape Flats WWTW in the Western Cape, South Africa. The facility's equipment is due for an upgrade and it was investigated if an improved process could be created. The base case of maintaining existing conventional mesophilic anaerobic digestion (MAD) was compared against the case of retrofitting THP. This would increase capacity and improve final product quality. The site would become a regional sludge facility importing additional sludge from some of the surrounding WWTWs. This would divert sludge from landfill and create more sustainable disposal options. Steady-state models were developed for the conventional MAD and THP-MAD. These models were developed to include a kinetics section, stoichiometry section and a weak acid/base chemistry section. The kinetics section used hydrolysis as the rate limiting step when applying saturation kinetics. A stoichiometry section takes input from the kinetics conversion and used the elemental compositions of both substrate and biomass while predicting the amounts of other AD products formed. The weak acid/base chemistry predicted pH and took into account corrections for ionic strength and temperature, which were found to be particularly applicable in the case of high solids THP digestion with the elevated dissolved concentrations. Many of the WWTW's in Cape Town make use of nitrification-denitrification biological excess phosphorous removal (NDBEPR) activated sludge (AS) treatment, often preceded by primary sedimentation. The modelling thus considered a 60:40 mixture of NDBEPR wasted activated sludge (WAS) and primary sludge (PS). AD modelling accounted for the breakdown of polyphosphate (PP) with the uptake of readily biodegradable COD to form poly3- hydroxybutyrate (PHB). The models also predicted the extent of spontaneous magnesium ammonium phosphate (struvite) precipitation inside the digester, and as well as the effect this would have on digester alkalinity and pH. Results showed that when THP is retrofitted 2.5 times more sludge could be processed using the existing digesters' volume i.e. without building any additional digesters. This results in sludge treatment throughput increasing from 60 dry tonnes of solids per day for conventional digestion to 153 dry tonnes per through advanced THP digestion. Modelling has shown in each case that important AD parameters, such as free ammonia concentration, pH, alkalinity, and methane production are within the correct range for stable digester operation while sludge stability was achieved. Major operating expenses and savings were evaluated. It was estimated that retrofitting THP created a saving of over R70mil/annum, largely due to savings in sludge disposal, and produce 2.7MW of surplus electrical energy. Carbon emissions were assessed for each case with THP digestion reducing significantly more emissions than conventional digestion. Additional investment required to upgrade conventional digestion to THP digestion specifically at the Cape Flats WWTW site would create a payback of between 5 to 6 years.